Effects of external loading on power output during vertical jump: a pilot study with water polo goal keepers - Corrêa, S. C.; de M. Bertuzzi, R. C.; Romano, R. G.; Alves, F.; Guimarães, G. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study was to describe preliminary results of the effects of external loading on power output during vertical jumps performed on a force platform by three elite water polo goal keepers (1 female and 2 male). Peak power output was calculated from time-force curves during vertical jumps with and without external additional loads corresponding to 0%, 5%, 10% and 15 % of their body weight. The jumps were performed from a squat position, without lower limb counter-movement or arm swings. The peak instantaneous power was reached at 0% additional load (body weight) by two of the athletes, and for the third, the peak instantaneous power was reached at 5% additional load. This study suggests that for water polo goal keepers, the load that generates maximum power output in dry land exercises is body weight, without any additional load.